Why have target-date funds performed better in the COVID-19 selloff than the 2008 selloff? - Mao, Mike Qinghao; Wong, Ching Hin (Journal of Banking & Finance, 2022)
We document a reduction in both the level and cross-sectional dispersion of systematic risk in the target-date fund (TDF) market after 2008, which resulted in better performance of TDFs during the COVID-19 selloff compared to the 2008 selloff and a reduction in TDF return dispersion. We find that the shift is more pronounced in close-to-retirement funds and driven by the TDF series investing more in equities in the early period, consistent with TDFs catering to the market demand for lower risk exposure after the 2008 crisis. In addition, TDF systematic risk shifters do not exhibit more idiosyncratic risk-taking.